Patient-oriented intervention in addition to centrally organised checkups improves diabetic patient outcome in primary care. Issue 5 (8th October 2008) - Meulepas, M A; Braspenning, J C C; de Grauw, W J; Lucas, A E M; Wijkel, D; Grol, R P T M
Abstract : Background: Logistic support to general practitioners improves the care processes for patients with diabetes but is not sufficient to meet all criteria. Aim: To introduce patient-oriented interventions by a practice nurse in general practices which already use logistic support to improve the care processes for patients with diabetes. Design of study: A controlled before–after study with delayed intervention in the control group. Setting: 51 practices (n = 23 for the intervention and n = 28 for the control group) in the south of The Netherlands and 900 of their patients with type 2 diabetes. Methods: Data were collected on the results of the checkups (fasting blood glucose, glycosylated haemoglobin (HbA1C), cholesterol, cholesterol/high-density lipoprotein ratio, triglycerides, creatinine, blood pressure, fundus photo, foot exam and body mass index), smoking status, physical activity and medication use. The effect of the patient-oriented intervention was analysed in a mixed model with repeated measurement covariance structure. Results: The HbA1C improved in the intervention group (from 7.3 to 7.1), while that of the control group deteriorated (from 7.2 to 7.3). The percentage of patients with an HbA1C ⩾8.5 was halved after the intervention (from 13 to 6). Patients in the intervention group started to exercise more besides their daily activities compared with the control group. The need for medication increased more in the control group than in the intervention group (more changes to insulin and more defined daily dose (DDD) oral medication). Conclusion: Patient-oriented interventions in addition to logistic support have a positive effect on diabetic patient outcomes.